Business Risk Modelling Using Maqasid Sharia For Islamic Bank Financing Decisions - Agung Nugraha, Aditya; Sain, Zohaib Hassan; Sartika, Mila; AGOI, Moses Adeolu (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2025)
This research aims to model business risk based on Maqasid Sharia as a framework for financing decision-making at Bank Syariah Indonesia (BSI) Pekalongan Branch. This study departs from the increasing complexity of financing risks amid demands for compliance with Sharia principles and financial stability. This study seeks to answer the question of the extent to which Maqasid Sharia values, such as hifz al-mal (property protection), hifz al-nafs (protection of life and welfare), and hifz al-din (protection of religious values), can be integrated into the risk management and decision-making process of Islamic bank financing. This study employs a qualitative-descriptive approach, collecting data through in-depth interviews, field observations, and an analysis of financing documents at the BSI Pekalongan Branch. The data was analysed thematically by linking empirical practices and Maqasid Sharia theory in the study of business risk management. The study results show that the application of Maqasid Sharia values has been gradually internalised in feasibility analysis, contract determination, and financing monitoring. The principle of hifz al-mal is the basis for prudent protection of banks' and customers' assets. Hifz al-nafs directs policies towards businesses oriented towards social benefits, and hifz al-din ensures compliance with Sharia fatwa and Islamic business ethics. The integration of these values has been proven to reduce non-performing financing (NPF) and strengthen customer confidence. The implications of this study confirm that maqasid Sharia plays a role as a meta-framework in risk management, which can simultaneously balance financial and moral goals. These findings offer a theoretical contribution to expanding the Sharia risk management paradigm and opening space for developing value-based risk models to support sustainable financing practices in the Islamic banking sector.